Noisy Management: A History of Danish School Governing from 1970-2010 - Justine Grønbæk Pors (Copenhagen Business School (CBS), 2011)
In Denmark, as in many other welfare states, we strongly believe that problems within the public sector can be solved by means of better management. For quite some years it has been assumed that management leads to more control over and better quality of welfare. Politicians and public servants have therefore been concerned with how the individual hospital, nursing home and school can develop its management. This has created a somewhat strange problem: How is it possible from a position at the top of a governing hierarchy to create management capacity from below? This thesis is about how Danish local government, municipalities, have developed understandings of governing relations between themselves and the public school over the last 40 years. The thesis tracks how municipalities have gradually assigned organizational independence to the individual school and increased their expectations of its self-management....
hdl:10398/8355
Keywords: 650